Malignant pleural mesothelioma with lacrimal gland metastasis. (16th July 2016) - Hanafi, Hanida; Verdijk, Rob M.; Paridaens, Dion
Abstract: Purpose: To describe a rare clinical case of biopsy‐proven metastatic mesothelioma of the lacrimal gland which responded well to chemo and radiation therapy. Methods: Interventional case report. Results: A 55‐year‐old woman with an untreated malignant biopsy‐proven pleural mesothelioma presented with right proptosis, diplopia and hypoglobus. Magnetic resonance imaging showed an aggressive lacrimal gland tumour with bony erosion. A biopsy concluded a diagnosis of metastatic mesothelioma of the lacrimal gland. Her lacrimal and lung tumours showed a marked regression following palliative chemo (carboplatin) and radiation therapy. Conclusions: Malignant pleural mesothelioma may metastasize to the orbit, including the lacrimal gland. A combined chemo and radiation therapy may reduce the size of the metastatic and primary tumour.